To determine if the values -1 and 73 are solutions to the equation \(3x^2 - 4x - 4 = 3\), we first need to simplify the equation.
Rearranging the equation gives us: \[ 3x^2 - 4x - 4 - 3 = 0 \] \[ 3x^2 - 4x - 7 = 0 \]
Next, we can check if -1 and 73 are solutions by substituting them into the equation.
-
For \(x = -1\): \[ 3(-1)^2 - 4(-1) - 7 = 3(1) + 4 - 7 = 3 + 4 - 7 = 0 \] So, \(x = -1\) is a solution.
-
For \(x = 73\): \[ 3(73)^2 - 4(73) - 7 = 3(5329) - 292 - 7 \] \[ = 15987 - 292 - 7 = 15987 - 299 = 15688 \quad (\text{not } 0) \] So, \(x = 73\) is not a solution.
Thus, the statement "The values -1 and 73 are both solutions to the quadratic equation \(3x^2 - 4x - 4 = 3\)" is False.
Now, for Question 2, since the above statement was false, the correct response would be: "Only -1 is a solution to \(3x^2 - 4x - 4 = 3\)".
So, to summarize:
- False
- Only -1 is a solution to \(3x^2 - 4x - 4 = 3\).